Secretion and endocytosis in subapical cells support hyphal tip growth in the fungus Trichoderma reesei - Martin Schuster; Sreedhar Kilaru; Han A. B. Wösten; Gero Steinberg (Nature Communications)
Abstract Filamentous fungi colonise substrates by invasive growth of multi-cellular hyphae. It is commonly accepted that hyphae expand by tip growth that is restricted to the first apical cell, where turgor pressure, exocytosis and endocytosis cooperate to expand the apex. Here we show that, contrary to expectations, subapical cells play important roles in hyphal growth in the industrial enzyme-producing fungus Trichoderma reesei. We find that the second and third cells are crucial for hyphal extension, which correlates with tip-ward cytoplasmic streaming, and the fourth-to-sixth cells support rapid growth rates. Live cell imaging reveals exocytotic and endocytic activity in both apical and subapical cells, associated with microtubule-based bi-directional transport of secretory vesicles and early endosomes across septa. Moreover, visualisation of 1,3-β-glucan synthase in subapical cells reveals that these compartments deliver cell wall-forming enzymes to the apical growth region. Thus, subapical cells are active in exocytosis and endocytosis, and deliver growth supplies and enzymes to the expanding hyphal apex.